Circulating Strains of Brucella abortus in Cattle in Santo Domingo De Los Tsáchilas Province – Ecuador - Rodríguez-Hidalgo, Richar Ivan; Contreras-Zamora, Javier; Benitez Ortiz, Washington; Guerrero-Viracocha, Karina; Salcan-Guaman, Holger; Minda, Elizabeth; Ron Garrido, Lenin (Frontiers in Public Health, 2015)
In Ecuador, the Province of Santo Domingo de los Tsáchilas represents the largest informal market of livestock due to its strategic position in the country; thus, given the high mobility of cattle in this region, the aim of this study was to determine the strain variation of Brucella sp.. Part of the study was the isolation, biotyping and genotyping of Brucella species isolated from milk and supra-mammary lymph nodes of sero-positive bovines. Protocols used for isolation, biotyping and genotyping of Brucella species were selective Farrell medium, biochemical assays and IS711-PCR, AMOS-PCR and HOOF-Prints techniques, respectively. In total, 656 animals from sero-positive dairy herds and from the slaughterhouse of the province were diagnosed by Rose Bengal and Wright’s Slow Agglutination test with EDTA. From these animals, 50 animals were found sero-positive for brucellosis. Twenty-five lymph nodes and 25 milk samples from each group of positive reactors were cultured and growth. Isolation was possible in 4 (16%) and 9 (36%), respectively; and of these, 10 isolates were diagnosed as Brucella sp. All 4 isolates of lymphatic tissue corresponded to Brucella abortus biotype 1, confirmed as field strains by molecular analysis. Milk isolations, biochemically showed a more dispersed pattern in which B. abortus biotypes 1 and 4 were found; yet four samples gave a pattern similar to B. abortus biotype 2; however, only biotypes 1 and 4 were confirmed by molecular analysis. The concordance between biochemical and molecular diagnostic tests reached 76.9%.